Identification of potent schistosomicidal compounds predicted as type II-kinase inhibitors against Schistosoma mansoni c-Jun N-terminal kinase SMJNK - Moreira, Bernardo P.; Gava, Sandra G.; Haeberlein, Simone; Gueye, Sophie; Santos, Ester S. S.; Weber, Michael H. W.; Abramyan, Tigran M.; Grevelding, Christoph G.; Mourão, Marina M.; Falcone, Franco H. (Frontiers in Parasitology, 2024)
Schistosomiasis has for many years relied on a single drug, praziquantel (PZQ) for treatment of the disease. Immense efforts have been invested in the discovery of protein kinase (PK) inhibitors; however, given that the majority of PKs are still not targeted by an inhibitor with a useful level of selectivity, there is a compelling need to expand the chemical space available for synthesizing new, potent, and selective PK inhibitors. Small-molecule inhibitors targeting the ATP pocket of the catalytic domain of PKs have the potential to become drugs devoid of (major) side effects, particularly if they bind selectively. This is the case for type II PK inhibitors, which cause PKs to adopt the so-called DFG-out conformation, corresponding to the inactive state of the enzyme. Therefore, the goal was to perform a virtual screen against the ATP pocket of the inactive JNK protein kinase. After virtually screening millions of compounds, Atomwise provided 85 compounds predicted to target human JNK as type II inhibitors. We have screened these selected compounds in vitro against larval stage (schistosomula) of S. mansoni using the XTT assay. Adult worms were assessed for motility, attachment, and pairing stability. In total, 33 compounds were considered active in at least one of the assays, and two compounds presented strong effects against both life stages. In conclusion, the approach to screen type II kinase inhibitors resulted in the identification of two potent compounds that can be further developed against schistosomiasis.